GOVERNANCE INNOVATION IN ADDRESSING UNDERNUTRITION AMONG UNDER-FIVE CHILDREN - Lidya Kusuma Pratiwi, Rita Rahmawati, Rusliandy (Integrative Perspectives of Social and Science Journal, 2026)
This study aims to analyze governance innovation in addressing undernutrition among toddlers through the “MARI PERGI KE BALI” program. The study examines governance innovation concepts, including content, context, and process dimensions. A qualitative descriptive approach was applied, involving health workers, community cadres, and mothers as participants. Data were collected through interviews, questionnaires, and documentation over a three-month period. The findings indicate that the program improves toddlers’ appetite and weight through the use of moringa-based nutrition and community engagement. However, challenges remain in participation and resource availability. The study implies that integrating technical interventions with community-based approaches is essential for sustainable public health outcomes.